ASSESSMENT OF THE DEGREE OF KNOWLEDGE OF DENTISTS REGARDING THE USE AND DISPOSAL OF RADIOGRAPHIC MATERIAL: Dentistry radiology and biosafety - Roman-Torres, Caio Vinicius G.; Pasquinelli, Fernanda; Domingues, Nilton Rodrigues A. P.; Placido Penna, Luiz Alberto (International Journal of Research -GRANTHAALAYAH, 2020)
Concern about the risks of radiation and the quality of the radiographic image has led many researchers and public agencies to carry out studies on the subject, which have found the existence of a series of problems in the practice of dental radiology. Based on the above, the objective of this study was to evaluate the knowledge and attitudes of dental surgeons regarding biosafety and the use of devices and materials used throughout the radiographic process in dental offices. 200 Dentists were interviewed with offices in some cities in the Baixada Santista region in the State of São Paulo, Brazil, variables such as age, gender, time since graduation, professional specialty, were only identified at the time of the interview. During the visit, the researcher assessed, by means of a questionnaire, components related to the radiological practice in the offices and about the attitudes during the radiological practice and, consequently, about the radiological protection rules adopted, either for the patients or professionals involved. When the questionnaire was applied, a statistically significant difference was observed in relation to the concept of biosafety 98% of the interviewees answered yes, that they know what biosafety is. If there are notices in the office warning about the x-ray equipment, 89% responded that they do not. The viewing of radiographs taken previously by the patients was indicated by 97.5% of the interviewed dentists, and 95% use breast and thyroid protection with a lead apron. More than half of the dentists, 52%, discard the substances used in the revelation process in the office sink. The results observed in our study are not encouraging, either due to the ignorance of the current legislation, the use of the devices inappropriately and the processing carried out with real chances of contamination of the environment, we believe that an increase in teaching and control of biosafety in dental radiology is necessary.